2021
DOI: 10.1007/978-981-16-4578-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behaviors of Long-Distance Truck Drivers

Abstract: Truck drivers are a group of recognized marginalized people who are sexually active during their long driving hours. Their exhausting working environment causing lethargy and mental fatigue stirs them to have sex (Essuon et al. in J Health Care Poor Underserved 20:40–52, 2009, [1]). Long-distance truck drivers transport goods over hundreds and even thousands of miles. They may drive flatbed rigs, which are used for carrying steel, or tankers and tractor trailers. They usually drive at night when traffic is lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, this assertion may not suffice for some regions like Latin America and the Caribbean, Eastern Europe and Central Asia, Middle East and North Africa and Western, Central Europe and North America, where a very low number of studies were identified. Indeed, the high burden of HIV may for long have been masked by the more attention given to other most-at-risk populations, somewhat isolating LDTDs in various HIV preventive and research programs owing to their hard-to-reach nature [83]. Furthermore, the high burden may infer delayed success of HIV prevention among this population, which consequentially derail the collective global efforts to fight the epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, this assertion may not suffice for some regions like Latin America and the Caribbean, Eastern Europe and Central Asia, Middle East and North Africa and Western, Central Europe and North America, where a very low number of studies were identified. Indeed, the high burden of HIV may for long have been masked by the more attention given to other most-at-risk populations, somewhat isolating LDTDs in various HIV preventive and research programs owing to their hard-to-reach nature [83]. Furthermore, the high burden may infer delayed success of HIV prevention among this population, which consequentially derail the collective global efforts to fight the epidemic.…”
Section: Discussionmentioning
confidence: 99%